RELATIONAL DIMENSION OF WOMEN IN SMALL BUSINESSES FOR THE VALUE CO-CREATION - Arena, Claudia; Catuogno, Simona; Kunz, Alberto; Pastore, Patrizia (Piccola Impresa / Small Business, 2025)
Purpose. Relationships are an important component for the growth of organizations. Through the original lens of dimensional publicness theory, this research aims to highlight the role of women in small businesses in co-creating economic, public, and social value through the relational dimension of capital. Methodology. A survey of the literature and visualization of the research field was conducted on a sample of articles concerning the topics of women in small businesses, relational capital and the value of entrepreneurial initiatives. Subsequently, a classification of the studies and a thematic analysis was carried out aimed at identifying the contribution of relational capital to the co-creation of value at different levels of publicness. Results. The literature was mainly developed in contexts characterized by a low level of publicness highlighting positive implications on value creation attributable to the relational dimension of capital. We propose a theoretical framework useful for capturing the extent to which the relational capital of women in small businesses contributes to the co-creation of value, complemented by the development of propositions to be tested empirically. Managerial implications. In order to increase the importance of the value co-created for the ecosystems by women in small businesses, policy makers could support programs that enable the development of women's business networks with public or publicly supported institutions where resources, knowledge and skills can be shared and systematized. Limits of the research. The research is based on a literature review conducted on a limited number of papers extracted from Isi Web of Knowledge and takes a purely theoretical approach. Originality. Overcoming the traditional dichotomy between the private and public sectors based on the proprietary nature of resources, the study contributes to the existing literature by identifying theoretical propositions based on the dimensional publicness approach to be empirically tested to enrich the understanding of the value of the relational dimension of women in small businesses for the value co-creation.